A Critical Review of Conceptual Framework of Service Quality: Clarifying the Concept of Service Quality (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Presented paper incorporates the jist of extensive conceptual review for a deeper and clear insight in the construct and concept of service quality. Service quality is one of the most researched and lucrative concept of service market research, yet the bequest of the concept is repeatedly debated on certain dubious aspects. Different studies have used variety of overlapping models consisting diverse variables. In fact various terms like service perception, service performance and perceived service quality have been used irrelevantly leading more confusion. In fact there is felt a confusion regarding relevance of measuring service expectations to measure service quality. Such confusion herein addressed in the paper to provide a clearer insight for further researches. Also, the research paper elaborated the widely used and selected five models of service quality in simpler way.